2017
DOI: 10.1016/j.virusres.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Avian infectious bronchitis viruses in Iran (2015–2017) reveals domination of IS-1494 like virus

Abstract: Avian infectious bronchitis virus (IBV) is causing major economic losses to the poultry industry. The analysis of the S1 gene has been used to determine IBV genotype. The aim of this study was genotyping of IBVs circulating among the Iranian broiler flocks in the period between 2015 to 2017. Trachea samples from 278 broiler flocks were collected from broiler farms in eight provinces of Iran. After Real-time RT-PCR, IBV-positive samples were further characterized based on S1 gene. The results of the Real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Overall, the four lineages were circulating in the 40 flocks. Since 1998, serotypes 793/B (GI-13 lineage) and Massachusetts (GI-1 lineage) have been the most common viruses in the Iranian farms [ 14 , 16 , 17 ]. However, there may have been other variants that probably have not been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the four lineages were circulating in the 40 flocks. Since 1998, serotypes 793/B (GI-13 lineage) and Massachusetts (GI-1 lineage) have been the most common viruses in the Iranian farms [ 14 , 16 , 17 ]. However, there may have been other variants that probably have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, there may have been other variants that probably have not been identified. Modiri et al [ 16 ] also attempted to genotype IBV circulating in the Iranian broiler flocks from 2015 to 2017 showed that 52.16% of the flocks were IBV-positive. These researchers reported variant -2 (IS-1494-like viruses) as the predominant type, followed by 793/B, Massachusetts, and QX-like viruses, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In study that was done by Modiri et al, bronchitis has posed to be a challenge in broiler farms of Iran's neighboring countries as well (Modiri Hamadan et al 2017). In an experiment relevant to Iraq during the years 2013-2014, 32 samples of IB virus were identified from 100 samples collected.…”
Section: Discussionmentioning
confidence: 99%
“…IS/1494/06 is one of the most prevalent IBV strains in poultry flocks in many countries, especially in the Middle East region, [ 14 16 ]. The purpose of this study was to acquire knowledge about the proteome of the kidney tissue of specific-pathogen-free (SPF) chickens infected with a local isolate of a nephrotropic variant 2 genotype (IS/1494/06).…”
Section: Introductionmentioning
confidence: 99%